2022
DOI: 10.1371/journal.pone.0275907
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the challenges to safer prescribing and medication monitoring in prisons: A qualitative study with health care staff

Abstract: Introduction Research suggests that patients who are prisoners experience greater morbidity, increased health inequalities and frequent preventable harm, compared to the general population. Little is known about the process and influencing factors for safe prescribing in the unique prison environment, which may limit the development efforts to improve the quality of care in prisons. This study aimed to understand the process and challenges associated with prescribing in prisons, explore the causes and impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…These include poor information technology, security rules for ambulance release or medication management, staffing levels, the availability of appropriately trained staff and prison overcrowding [15]. For example with prison electronic health records it has been reported how limitations affecting interfacing with external systems may delay verification of medication records if the information needed is not available when required [19], and there are ongoing discussions across UK healthcare considering how inter-operability and sharing of health information (including with patients) could address challenges such as these [56][57][58]. However, such issues can have deleterious consequences on physical and psychological morbidity, high rates of mortality, self-harm, and substance misuse [10].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…These include poor information technology, security rules for ambulance release or medication management, staffing levels, the availability of appropriately trained staff and prison overcrowding [15]. For example with prison electronic health records it has been reported how limitations affecting interfacing with external systems may delay verification of medication records if the information needed is not available when required [19], and there are ongoing discussions across UK healthcare considering how inter-operability and sharing of health information (including with patients) could address challenges such as these [56][57][58]. However, such issues can have deleterious consequences on physical and psychological morbidity, high rates of mortality, self-harm, and substance misuse [10].…”
Section: Plos Onementioning
confidence: 99%
“…For people detained in prison in England, the average age of death is 56 years [16]. Whilst people in prison may also access healthcare more often than those in the community [17,18], health practitioners deliver care where strict security regimes may take precedent [19]. The structure of secure environments may restrict the delivery of health care within and outside prisons, for example through high rates of missed hospital appointments [20] which may be due to a lack of security escort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such inequities in medication-related experiences and outcomes can occur in any stage of the medication use process, such as the prescription, dispensing and administration of medication, and a sample of these issues is presented in Table 2. The available evidence suggests that members of ethnic minority groups [4,5,[15][16][17][18][19][20], people who are institutionalised [17,21], incarcerated [22,23] or homeless [24][25][26] and people of sexual minority groups [27] are more likely to experience medication-related problems than the general population. This is also true for people with certain health statuses, such as those with sensory impairment, either auditory or visual [17,28], older people with intellectual disabilities [29] and those who experience cognitive impairment, severe mental illness and frailty [17].…”
Section: Do Marginalised Groups Experience the Same Medication-relate...mentioning
confidence: 99%
“…For example, these people experience a higher prevalence of morbidity, polypharmacy, mental health and substance misuse issues than the general population. These patient-level factors add complexity to the individual factors, e.g., the prescriber, and organisational factors, e.g., the integration of information, in these contexts [22][23][24][25]36,37]. We identified one study that reported the patients' perspectives of their issues or needs in the homeless setting and none referring to the prison setting [25].…”
Section: What Are the Causes Of Inequity In Medication-related Outcom...mentioning
confidence: 99%